O mesmo te quero - Wolff, Renata Fonseca (2021)
This dissertation consists of a piece of fiction (a novel), accompanied by a theoretical-reflective essay which supports and precedes it. Its starting point is the short story “So feared a hell”, by Uruguayan writer Juan Carlos Onetti. It adopts a version of the character of Gracia César, this time shifted towards formal centrality in the narrative, as a way of reconstructing (fictionally, with implied intertextuality), expanding and complicating her character as well as the actual events that inspired Onetti’s creation. The creative text’s immediate narrative axis follows the actress from 1976 to 1977, as she prepares for a much anticipated dramatic début in the theatre. In other axes, and going back chronologically, there are the actress’s journeys as she begins her career in early 1950s’ Argentina, concurrent with those of another character, a journalist in the early stages of a story on the brink of the civilian-military dictatorship installed in that country in 1976. The reflective essay describes the origins of the narrative’s conception, the research undertaken in its development, and the impact of that research upon the creative piece’s format and matter. It also contains a theoretical study of Juan Carlos Onetti’s position as author and reader of his own work, as well as of the structure and themes of the short story “So feared a hell” that substantiate the desire to weave a fictional piece centered around Gracia as its main character.